Analisis Tingkat Kepatuhan Pengelolaan Data Pribadi Pengguna Terhadap Undang-Undang Perlindungan Data Pribadi (UU PDP) Pada Platform Digital - Chery Rahayu Lestari; Azifa Balqis Az'zahra; Nadhiya Mozza Octavia; Fouziah Khenia Br S. Pandia; Ririn Wirdani; Said Hambali Takhir (PT. Meja Ilmiah Publikasi, 2026)
The rapid development of digital platforms has intensified the collection and processing of users’ personal data, thereby increasing the risk of privacy violations when data management practices are not aligned with applicable legal provisions. This study aims to analyze the compliance of personal data management practices on digital platforms with Indonesia’s Personal Data Protection Law (Law Number 27 of 2022). This research employs a descriptive qualitative method using a documentation study approach. Data were obtained through an analysis of privacy policies, terms and conditions of service, and official documents related to personal data management published by digital platforms, which were subsequently examined in reference to the provisions and principles stipulated in the Personal Data Protection Law. The findings indicate that transparency in personal data management generally complies with the legal requirements, particularly regarding the disclosure of data types and processing purposes. However, several aspects, including consent for data processing, data security and confidentiality, purpose limitation and data retention, as well as the fulfillment of data subject rights, remain only partially compliant. These results demonstrate that the implementation of personal data protection on digital platforms still requires stronger regulatory compliance and more comprehensive protection mechanisms. This study is expected to contribute to the evaluation and improvement of legal compliance and governance of personal data management within digital platforms